Studies on fatigue behaviour of weld-bonds of Al-Mn-Mg alloy - Mittal, Mayank; Dwivedi, Dheerendra (Cranfield University Press, 2013)
In the present paper, fatigue and metallurgical behaviour of weld-bonds and adhesive bonds developed using 2 mm thick aluminium alloys namely 5052 alloy have been reported. Weld-bonds were prepared using structural adhesive (Epoxy resin) and spot welding (20 kA welding current for 6 cycles welding time at welding pressure of 0.5 MPa). Curing after applying Epoxy resin for developing adhesive bonds and weld bonds was performed at a temperature of 100 oC for 90 min. Fatigue tests were conducted under tension–shear loading pattern with stress ratio of 0.5 and loading frequency of 5 Hz. The maximum tensile shear load for fatigue test was kept at different level i.e. 90%, 80%, 70% and 50% of the ultimate shear tensile strength of weld bond and adhesive bonds. The fatigue lives of both adhesive bond and weld-bond joints decreased with increase in maximum tensile shear load. Fatigue performance of weld bond was higher than adhesive bond especially at high load.
Keywords: 5052 Aluminium alloy; weld bonding; mechanical properties